Tình hình nhiễm Staphylococcus aureus từ năm 2005 đến 2008 tại BVTW Huế - Liên, Nguyễn Thị Nam; Dung, Châu Thị Mỹ; Hòa, Nguyễn Văn; Lan, Lê Thị Thanh; Lợi, Lê Thị; Luyện, Trần Hữu (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.